Marfan Syndrome, A Review - Gerard Pals (Faculty of Medicine, Diponegoro University, 2018)
Marfan syndrome is named after the French pediatrician Antoine Bernard-Jean Marfan who described in 1896 a girl with arachnodactyly and long limbs1. The patient also had congenital contractures of the elbows and would not fulfill the current criteria for Marfan syndrome. She probably was suffering from a condition that we now call contractural arachnodactyly, caused by mutations in the FBN2 gene.The clinical features of Marfan syndrome affect many systems of the body. The most obvious are the skeletal features, long limbs, tall stature, long thin fingers (arachnodactyly or spider fingers). The skeletal features can be scored objectively as: arm span more than 1.05 x body length; wrist sign (thumb and index finger can encircle the wrist of the other hand with at least one digit overlap) and thumb sign (when making a fist around the thumb, one digit of the thumb sticks out). The main neurological symptom is dural ectasias. The most severe symptoms are cardiovascular: mitralis valve prolapse, aortic dilatation and thoracic aortic aneurysms and dissections, which may lead to sudden death5. However, I noticed in discussions with patients that they often consider the ocular symptoms, severe myopia and lens luxation, the worst for themselves, because the latter may lead to blindness.